The influence of Hegel's philosophy on Marxist philosophical thought - Hanh, Than Thi; Thanh, Phan Thi (Kalágatos, 2025)
The current context of increasing global inequality, economic instability, and political polarization underscores the need to re-examine foundational theories that address social change and class conflict dynamics. This study investigates the significant impact of Hegelian philosophy on the formation of Marxist thought, specifically how Karl Marx and Friedrich Engels incorporated and transformed Hegel's dialectical method into a materialist framework. The research focuses on critical aspects of Hegelian dialectics, such as the synthesis of contradictions. It explores how these were reinterpreted to create Marx’s dialectical materialism, emphasizing the role of material conditions and social relations in shaping history and society. The research method involves a critical analysis of primary texts by both Hegel and Marx, as well as secondary literature that traces the development of Marxist theory from its Hegelian roots. By examining how Marx and Engels transitioned from Hegel's idealism to materialism, the study highlights the importance of understanding the economic base of society and its influence on cultural and political structures, a concept known as historical materialism. The findings demonstrate that Marx's critique of ideology, derived from Hegelian ideas, remains crucial for understanding how dominant ideologies serve to maintain the power of the ruling classes. This research is significant because it offers a deeper understanding of Marxism's theoretical foundations, which continue to inform contemporary social and political analysis. The relevance of this study lies in its potential to provide insights into ongoing issues of class dynamics, inequality, and social change in the modern world.